Sustainable Land Management Supports Organic Farming in Tidal Swamp Area of South Kalimantan: Water Quality - Zuraida Titin Mariana; Muhammad Mahbub; Afiah Hayati (Journal of Wetlands Environmental Management, 2015)
Development of organic farming in tidal land should be wise and considers all aspects supporting the development of sustainable agriculture. The aim of this research was to quantify concentration of metals contained in tidal swamp water both at the single and double tides of various tidal typologies, including Pb, Cd, Cr, and Fe ions. The research was conducted in four villages in Barito Kuala regency (South Kalimantan) to represent tidal land types A, B, C and D, respectively. Sampling was carried out at spring and neap tides in each villages and the Barito river nearest to the villages. The water samples were collected in plastic bottles in the irrigation canals and brought to the laboratory for analysis of Pb, Cd, Cr and Fe concentrations.Â  The results showed that the Pb, Cd, Cr and Fe concentrations in studied area were <0.002 - 0.0122 ppm, 0.0067 - 0.0122 ppm, <0.002 - 0.0064 ppm and 0.0358 ppm - 9.0807 ppm for Pb, Cd, Cr and Fe, respectively. Based on he limiting factor in heavy metals of water quality for agricultural crops in land C and D type are cadmium (Cd) and iron (Fe) elements. Acidity of water on the land types C (pH 2.72 - 2.95) and D (pH 2.68 - 4.41) were lower than those in the land types A (pH 6.01 - 6.83) and B (pH 3.6 - 6.29).